A generalized fuzzy linear programming approach for environmental management problem under uncertainty - Fan, Yurui; Huang, Guohe; Veawab, Amornvadee (Journal of the Air & Waste Management Association (1995), 2012)
In this study, a generalized fuzzy linear programming (GFLP) method was developed to deal with uncertainties expressed as fuzzy sets that exist in the constraints and objective function. A stepwise interactive algorithm (SIA) was advanced to solve GFLP model and generate solutions expressed as fuzzy sets. To demonstrate its application, the developed GFLP method was applied to a regional sulfur dioxide (SO 2 ) control planning model to identify effective SO 2 mitigation polices with a minimized system performance cost under uncertainty. The results were obtained to represent the amount of SO 2 allocated to different control measures from different sources. Compared with the conventional interval-parameter linear programming (ILP) approach, the solutions obtained through GFLP were expressed as fuzzy sets, which can provide intervals for the decision variables and objective function, as well as related possibilities. Therefore, the decision makers can make a tradeoff between model stability and the plausibility based on solutions obtained through GFLP, and then identify desired policies for SO 2 -emission control under uncertainty.